PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MASALAH DAN PROYEK UNTUK PENGUATAN PROFIL PELAJAR PANCASILA BAGI PENDIDIK PAUD - sutama, i wayan; Astuti, Wuri -; -, Pramono -; Anisa, Nur; Wulandari, Helnia -; Permatasari, Intan - (Jurnal Graha Pengabdian, 2023)
Abstract: Problems in the field show that in Kepanjenkidul District there is only one teacher and driving school available. Teachers admit to experiencing the problem of a lack of information sources for studying the independent curriculum, including the project to strengthen the profile of Pancasila students. Most of the learning references only come from PMM (Merdeka Mengajar Platform). Therefore, this training was carried out as an answer to the problems faced by teachers in the form of investment actions in developing project-based learning tools to strengthen the profile of Pancasila students for educators to increase HOTS and Pancasila character in children. This training was carried out for 2 days. The flow included in-depth study of the material, case analysis in the form of RPP documents and video examples of children's learning activities, workshops, peer and expert reviews, Forum Group Discussion (FGD), field trials, draft revisions, compilation of participant projects, and book publication by the service team. The results of this activity show that the teacher is competent in compiling teaching modules with a score of 82, competent in formulating learning objectives with a score of 86, competent in designing problem and project based learning with a score of 85, competent in utilizing multi-sources and media as well as materials and tools with a score of 82 , and competent in designing authentic assessments with a score of 84.